Pengembangan E-LKPD Berbasis Kearifan Lokal Kerajinan Anyaman Bambu Model Project Based Learning - Hizbi, Tsamarul; Novianti, Baiq Aryani; Wajdi, Badrul; Yuliani, Epi (Universitas Hamzanwadi, 2023)
This research aims to develop E-LKPD based on local wisdom of Loyok bamboo woven crafts with a project-based learning model on Newton's Law material for class X SMA/MA Science. This type of research is research and development with a 4D model (define, design, development, disseminate). Product testing is carried out through validation by material experts, media experts and physics subject teachers as well as student responses in the form of practicality tests. The data collection instrument uses expert validation questionnaires and student responses. The data analysis technique uses validator and student data tabulation, then calculates the average score, and calculates the score percentage. Based on validation from 3 material experts, it shows a percentage of 86% with a very feasible category, the assessment of 3 media experts shows that the quality of E-LKPD is included in the very feasible category with a percentage of 81%, and the results of the assessment of 2 physics subject teachers show that the quality is E -LKPD is included in the very feasible category with a percentage of 84%. Meanwhile, the response results from 11 students showed that 90.9% of respondents stated that the criteria were very practical and 9.1% of respondents stated that they were practical.